Reforming the public administration: The role of crisis and the power of bureaucracy - Zareh Asatryan; Friedrich Heinemann; Hans Pitlik (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2015)
The need to balance austerity with growth policies has put government efficiency high on the economic policy agenda in Europe. Administrative reforms which boost the efficiency of the administration can alleviate the trade-off between consolidation and public service provision. Against such backdrop, this study explores the determinants of efficiency enhancing public administration reforms for a panel of EU countries using a novel reform indicator. The findings support the political-economic reasoning: An economic and fiscal crisis is a potent catalyst for reforms, but a powerful bureaucracy effectively constrains the opportunities of a crisis to promote this particular type of reform. Furthermore, there is evidence for horizontal learning from other EU countries, and for vertical learning associated with a particular type of EU transfers.
urn:nbn:de:bsz:180-madoc-396155
Keywords: H83; H11; D73; 330; Euro-crisis; public sector efficiency; cohesion policy; theory of bureaucracy